Preparation of future higher school teachers to designing of professionally-oriented teaching technologies - Naboka, Olga (ScienceRise: Pedagogical Education, 2018)
The article reveals the main components of the process of designing professionally-oriented learning technologies. Different approaches to the design of teaching technology through its stages are analyzed; consideration in the process of designing the features of the type of technology being designed; definition and further designing of a set of actions of the teacher within the limits of technologies, etc. Taking into account the tendencies of updating and modernizing the educational process, the conceptual framework for the training of future high school teachers to designing professionally-oriented technologies is based on an understanding of professionally oriented learning technology as a system of forms, methods, techniques and means aimed at guaranteeing the achievement of the objectives of professional training and bringing it as close as possible to the conditions of professional activity, ensuring the formation of a competitive labor market specialist. Designing professionally-oriented learning technologies takes place in accordance with the principles of system integrity; diagnostic, differentiated purposefulness; stimulating and motivating a positive attitude of students towards learning; flexible algorithm and variability of training; professional expediency; synergistic information support of training. System in the design process is provided by a combination of such components of professionally-oriented learning technology: targeted, informative, procedural-activity, diagnostic-corrective. The prevailing conditions for the use of professionally-oriented learning technologies are the creation of an appropriate educational environment for a higher education institution, where the introduction of the specified didactic system is in place, as well as the provision of a positive psycho-emotional climate in the process of professional training, systematic implementation of the subject of subjective interaction between students and teachers; active stimulation of students for self-education, self-training, self-development; an individualized choice of the type of professionally-oriented learning technology; application of innovative professional-oriented pedagogical tools for professional training